Visual literacy - Elkins, James, 1955- (New York ; London : Routledge, 2008)
- Visual literacy or literary visualcy? ##- Four fundamental concepts of image science / W.J.T. Mitchell ##- The remaining 10 percent : the role of sensory knowledge in the age of the self-organizing brain / Barbara Maria Stafford ##- Nineteenth-century visual incapacities / Jonathan Crary ##- From visual literacy to image competence / Jon Simons ##- The visual complex : mapping some interdisciplinary dimensions of visual literacy / Peter Dallow ##- Visual literacy in North American secondary schools : arts-centered learning, the classroom, and visual literacy / Susan Shifrin ##- Philosophical bases for visual multiculturalism at the college level / William Washabaugh ##- Bridging the gap between clinical and patient-provided images / Henrik Enquist ##- The image as cultural technology / Matthias Bruhn and Vera Dunkel ##- Visual literacy in action : "law in the age of images" / Richard K. Sherwin.
"This book began as a conference and exhibition held at University College, Cork in Ireland, in April 2005"--Pref.
Includes bibliographical references and index.
Selected papers. Based on those presented at the conference.
boek